KOMUNIKASI TENTANG KEPANGKATAN DOSEN FIKOM UPDM (B) - Sundoro, Panggih (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2006)
This happened to Moestopo University in particular the Faculty of Communication, before year 1990 was still predominated among the academic categories by only and handful qualified lectures. The majority who  spend  much of their day as governmental  officials and  who  should  perhaps  be  classified  as- academic  staff  as  well without academic_rank.Because the University reflects the intelectual and educational status of the society that spawn them, it comes as no surprise that  in the   terms   of  the   academic   model,   persons  who   give  lectures legitimately altared to the convensational Conception in advancement to rise ranks in lecturership. After years of the Communication Faculty Moestopo  University  as  an educational  institution  were  marked  by experimentation with   the  academic   content  and  forms.  The  first challengence was to rise ranks legitimately.First of all the latest trend in its education system, is putting the lecture  on communication and  information  sciences.  The  impact  of these changes, I   hope can solved the problems of to rise ranks legitimately and objective.